ATPR triggers acute myeloid leukaemia cells differentiation and cycle arrest via the RARα/LDHB/ERK‐glycolysis signalling axis. Issue 12 (11th May 2020) - Du, Yan; Zhang, Mei‐ju; Li, Lan‐lan; Xu, Xiao‐Lin; Chen, Hao; Feng, Yu‐bin; Li, Yan; Peng, Xiao‐qin; Chen, Fei‐hu
Abstract: Acute myeloid leukaemia (AML) remains a therapeutic challenge and improvements in chemotherapy are needed. 4‐Amino‐2‐trifluoromethyl‐phenyl retinate (ATPR), a novel all‐trans retinoic acid (ATRA) derivative designed and synthesized by our team, has been proven to show superior anticancer effect compared with ATRA on various cancers. However, its potential effect on AML remains largely unknown. Lactate dehydrogenase B (LDHB) is the key glycolytic enzyme that catalyses the interconversion between pyruvate and lactate. Currently, little is known about the role of LDHB in AML. In this study, we found that ATPR showed antileukaemic effects with RARα dependent in AML cells. LDHB was aberrantly overexpressed in human AML peripheral blood mononuclear cell (PBMC) and AML cell lines. A lentiviral vector expressing LDHB‐targeting shRNA was constructed to generate a stable AML cells with low expression of LDHB. The effect of LDHB knockdown on differentiation and cycle arrest of AML cells was assessed in vitro and vivo, including involvement of Raf/MEK/ERK signalling. Finally, these data suggested that ATPR showed antileukaemic effects by RARα/LDHB/ ERK‐glycolysis signalling axis. Further studies should focus on the underlying leukaemia‐promoting mechanisms and investigate LDHB as a therapeutic target.